Child abuse: children with disabilities - Palusci, Vincent J.; Kaplan, Richard Alan (Disability studies, 2017)
Introduction -- Children with disabilities / Vincent J Palusci, Dena Nazer, Donald E Greydanus, and Joav Merrick, New York University School of Medicine, New York, New York, USA, and others -- Aspects of maltreatment and disability -- Genetics, epigenetics and the molecular marks of stress : a primer / Kushol Gupta, Department of Biochemistry and Biophysics, Perelman School of Medicine, University of Pennsylvania, Philadelphia, Pennsylvania, USA -- Disability and the epidemiology of child abuse and neglect / Vincent J Palusci, New York University School of Medicine, New York, Frances L Loeb Child Protection and Development Center, Bellevue Hospital, New York, USA -- Conceptual framework and definitions of disability : an overview / Dilip R Patel and Kelly A Brown, Department of Pediatric and Adolescent Medicine, Western Michigan University Homer Stryker MD School of Medicine, Kalamazoo, Michigan, USA -- Abuse and neglect as cause for disability / Anastasia Feifer and Ingrid Walker-Descartes, David Geffen School of Medicine at UCLA, Los Angeles, California, and others -- Tragedy of sibling abuse of children with disabilities / Donald E Greydanus, Elizabeth K Hawver and Joav Merrick, Department of Pediatric and Adolescent Medicine, Western Michigan University Homer Stryker MD School of Medicine, Kalamazoo, Michigan, USA -- Disability and abuse : some international aspects / Joav Merrick, National Institute of Child Health and Human Development, Jerusalem, and others -- Assessment, treatment, reporting and prevention -- Evaluation of physical abuse and neglect in children with disabilities / Dena Nazer, Wayne State University School of Medicine, Children's Hospital of Michigan, Kids-TALK Children's Advocacy Center, Detroit, Michigan, USA -- Sexual abuse : medical evaluation and management in children with disabilities / Dena Nazer, Wayne State University School of Medicine, Children's Hospital of Michigan, Kids-TALK Children's Advocacy Center, Detroit, Michigan, USA -- Sexual behaviors in children and adolescents with developmental disabilities : assessment and treatment / Alyse Mandel and Ellen Datner, Bellevue Hospital Frances L. Loeb Child Protection and Development Center, New York City Health and Hospitals, New York, New York, USA -- Recognizing and responding to suspected maltreatment of children with medical complexity : medical neglect, medical child abuse and challenges facing families, mandated reporters and members of the health care and case planning teams / Alex Okun, New Alternatives for Children, New York, New York, USA -- Legal issues in child welfare cases involving children with disabilities / Frank E Vandervort and Joshua B Kay, University of Michigan Law School, Ann Arbor, Michigan, USA -- Preventing maltreatment in children with disabilities / Vincent J Palusci, New York University School of Medicine and the Frances L Loeb Child Protection and Development Center, Bellevue Hospital, New York, New York, USA -- Acknowledgements -- About the editors -- About the Frances l Loeb Child Protection and Development Center, Department of Pediatrics, New York University School of Medicine, New York, United States -- About the children's hospital of Michigan and the Wayne State University School of Medicine, Detroit, Michigan, United States -- About the Department of Pediatric and Adolescent Medicine, Western Michigan University Homer Stryker MD School of Medicine (WMED), Kalamazoo, Michigan, United States -- About the National Institute of Child Health and Human Development in Israel -- About book series "disability studies" -- Index